Inclusive Art Education of Uzbekistan in The Period of Independence - Egamberdiyev Murod Farhod ogli (Zien Journals, 2022)
The article presents a situational analysis of the development of inclusive art education, examines various models of teaching children with disabilities. The importance of inclusive art education for children with health problems is revealed, the possibilities and benefits of inclusion are described. The author of the article substantiates the merits of inclusive education for children in art schools
Keywords: Inclusion; creativity; art; inclusive model